Truth in many tongues : religious conversion and the languages of the early Spanish Empire - Wasserman-Soler, Daniel I. (Daniel Isaac), 1984- (The Pennsylvania State University Press, 2020)
"Examines how the Spanish monarchy managed an empire of unprecedented linguistic diversity, making only sporadic efforts to propagate Spanish during the sixteenth century. Challenges the assumption that the pervasiveness of the Spanish language resulted from deliberate linguistic colonization"--